Pengembangan Media Papan Hitung pada Materi Konsep Operasi Hitung Bagi Siswa Sekolah Dasar - Rahmawati Rahmawati; Ervi Rahmadani; Nasaruddin Nasaruddin (Indo-MathEdu Intellectuals Journal, 2023)
This research aims to determine the analysis of the needs for calculating board media, to describe the steps for developing calculating board media, material for the calculation operations of addition, subtraction, multiplication and division and to determine the validity of the calculating board media developed in class 3 of SDN 305 Langkidi. This research uses a type of development research using the ADDIE model. The steps taken in this research are needs analysis, design, product development and evaluation. The subjects of this research were 27 students and a class teacher. Data analysis uses qualitative and quantitative. The results of the calculation board media feasibility test from design experts obtained a percentage score of 71.87% in the valid category, while material experts got 84.37% which was also in the very valid category so that it could be used in learning.